2014
DOI: 10.1002/2014je004634
|View full text |Cite
|
Sign up to set email alerts
|

Surface albedo spectral properties of geologically interesting areas on Titan

Abstract: We investigate the nature and possible formation processes of three areas on Titan's surface which have been suggested as geologically interesting: Hotei Regio, Tui Regio, and Sotra Patera. We also reanalyze the spectral characteristics of the Huygens Landing Site. We apply a statistical Principal Component Analysis (PCA) and a radiative transfer (RT) method on the Visual and Infrared Mapping Spectrometer Datacubes in order to retrieve the surface albedo of distinct spectral units in the near infrared. We have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
67
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(69 citation statements)
references
References 93 publications
(257 reference statements)
2
67
0
Order By: Relevance
“…Different correction methods have been developed and applied to compensate for these effects. In this study, we will use two methods: a fast semiempirical correction for IR units identification and mapping purposes (Combes et al, 1997;Cornet et al, 2012;Coustenis et al, 2001Coustenis et al, , 2005Le Mouélic et al, 2012) and a comprehensive radiative transfer model in order to retrieve more precisely the albedo of the surface units and their composition (Hirtzig et al, 2013;Maltagliati et al, 2015;Solomonidou et al, 2014Solomonidou et al, , 2016Solomonidou et al, , 2018.…”
Section: Infrared Unit Mapping With Vims and Imaging Science Subsystemmentioning
confidence: 99%
See 1 more Smart Citation
“…Different correction methods have been developed and applied to compensate for these effects. In this study, we will use two methods: a fast semiempirical correction for IR units identification and mapping purposes (Combes et al, 1997;Cornet et al, 2012;Coustenis et al, 2001Coustenis et al, , 2005Le Mouélic et al, 2012) and a comprehensive radiative transfer model in order to retrieve more precisely the albedo of the surface units and their composition (Hirtzig et al, 2013;Maltagliati et al, 2015;Solomonidou et al, 2014Solomonidou et al, , 2016Solomonidou et al, , 2018.…”
Section: Infrared Unit Mapping With Vims and Imaging Science Subsystemmentioning
confidence: 99%
“…In Le , this IR-blue plume-shaped and dune-free area is suggested to be a sheet of icy deposits originated by a water vapor plume produced during the impact. Moreover, Solomonidou et al (2014) applied the Principal Component Analysis technique in order to calculate color units that each correspond to a unique spectral signature in the same VIMS cube as in Le and obtained the same results of three distinct regions. Figure 2b is a projected mosaic of three more recent VIMS high-resolution observations displayed with the same color scheme as in Figure 2a.…”
Section: Sinlap Cratermentioning
confidence: 99%
“…In addition, the rheology of methanol-containing slurries could have significant implications for the structure of possible cryovolcanic flows (Davies et al, 2010;Lopes et al, 2007;Zhong et al, 2009). Although there is not conclusive evidence for widespread cryovolcanic activity on Titan (Lopes et al, 2013;Moore & Pappalardo, 2011), there are regions for which it may be a reasonable explanation of topographic features (Lopes et al, 2013;Solomonidou et al, 2014), and it is one possible source of replenishment for Titan's atmospheric methane (Davies et al, 2016). Haghighi et al (2009), Vuillard andSanchez (1961), and Miller and Carpenter (1964), and adapted from Kargel (1992), Ott et al (1979), and Takaizumi and Wakabayashi (1997).…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned in Hirtzig et al (2013) and Solomonidou et al (2014), our model assumes a Lambertian surface, as is also the case in several other investigations (e.g. Griffith et al, 2012;Hayne et al, 2014).…”
Section: Analysis and Resultsmentioning
confidence: 91%
“…In particular, they show higher 5-lm reflectivity than any other observed region on Titan suggesting that their chemical composition is distinct from other regions (e.g. Barnes et al, 2005Barnes et al, , 2006McCord et al, 2006McCord et al, , 2008Mitri et al, 2008;Nelson et al, 2009a;Soderblom et al, 2009;Solomonidou et al, 2014, SA14 from now on). In addition, topographic information (Stiles et al, 2009) indicated that both Tui and Hotei are regional basins (in the case of Hotei Regio the central basin is surrounded by a higher mountainous terrain) including interesting morphological features such as radar dark and bright patches with sharp boundaries (e.g.…”
Section: Observations and Datamentioning
confidence: 82%